Manual for promoters of justice, peace, and integrity of creation (Claretian Publications, 1998)
A manual to help Justice, Peace and Integrity of Creation (JPIC) promoters to connect their mission statement with today's current events. It also contains guidelines on possible actions to take and is divided into five main themes: Reading the Signs of the Times, Biblical Foundations for JPIC, The Social Teaching of the church and Social Analysis, Re-imaging Religious Life and Re-imaging Mission.